2012
DOI: 10.4102/ojvr.v79i2.483
|View full text |Cite
|
Sign up to set email alerts
|

Immunogeno: Protective mechanism for Rift Valley fever in the Democratic Republic of Congo

Abstract: Rift Valley fever (RVF) is an acute, fever causing viral disease that affects domestic animals and humans. In Democratic Republic of Congo (DRC), this pathology is not well documented. No epidemic of the RVF has not been reported but sera samples collected in six provinces surveyed from 2005 to 2006 revealed 14% of apparent prevalence and, high apparent prevalence (20%) of antibodies against RVF virus was reported in Katanga Province during the same survey; this serological evidence was associated with abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…3,5,9,21 However, a number of live-attenuated RVF vaccine strains cause fetal malformations of the central nervous system and the musculoskeletal system that include spinal hypoplasia; hydranencephaly; hypoplasia of the cerebrum, cerebellum, and spinal cord; brachygnathia; arthrogryposis and scoliosis; brachygnathia inferior and arthrogryposis. 8,12,15 Therefore, natural RVFV infection with wild-type virus is not a differential diagnosis when fetal malformations are encountered in sheep. However, ill-advised use of live attenuated vaccines in ewes in the first or second trimester of pregnancy should be investigated if fetal malformations are reported.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,9,21 However, a number of live-attenuated RVF vaccine strains cause fetal malformations of the central nervous system and the musculoskeletal system that include spinal hypoplasia; hydranencephaly; hypoplasia of the cerebrum, cerebellum, and spinal cord; brachygnathia; arthrogryposis and scoliosis; brachygnathia inferior and arthrogryposis. 8,12,15 Therefore, natural RVFV infection with wild-type virus is not a differential diagnosis when fetal malformations are encountered in sheep. However, ill-advised use of live attenuated vaccines in ewes in the first or second trimester of pregnancy should be investigated if fetal malformations are reported.…”
Section: Discussionmentioning
confidence: 99%
“…A low rate (4%) of IgG antibodies from human against RVFV was reported in 1998 from Kisangani in the north-eastern region [11]. In 2009, Mulumba et al [34] reported a seroprevalence of 20% among cattle in Katanga in the southern region. In 2018, a seroprevalence (IgG and IgM) of 2-16% among cattle was reported in three provinces (Nord-Kivu, Sud-Kivu, Ituri) from the eastern region [35].…”
Section: Rift Valley Fevermentioning
confidence: 98%
“…The RVFV MP-12 strain (rMP-12) and RVFV MP-12 strain expressing eGFP (rMP-12-eGFP) were rescued through the reverse genetics approach (Ikegami et al, 2006). The recombinant human adenovirus serotype 5 vector was developed and maintained by the Beijing Institute of Biotechnology (Hunter et al, 2002;Wilson et al, 2014;Harmon et al, 2020)…”
Section: Cells Viruses and Animalsmentioning
confidence: 99%
“…Nonetheless, some serious adverse events induced by MP-12 have also been reported. The vaccine was elucidated to induce hepatocellular degeneration and necrosis in calves (Wilson et al, 2014) and teratogenic effects and abortions in sheep (Hunter et al, 2002). The formalin-inactivated vaccine NDBR-103 elicited a relatively high immune response, and 40 of 43 persons produced neutralizing antibodies of log 2 or more after a three-dose primary series immunization (Randall et al, 1962).…”
Section: Introductionmentioning
confidence: 99%